Effect of COVID-19 on Menstruation: An Observational Study - Singh, Muskan; Kaur, Manjinder; Verma, Anjana; Sharma, Nalini (Indian Journal of Community Health, 2023)
Introduction: COVID-19 patients have been reported to have systemic complications. Analyzing its effect on the endocrine system is essential to ensure women’s reproductive health. Aim: This study aimed to determine the effect of COVID-19 disease on menstruation. Methods: It was a hospital-based cross-sectional study conducted from October 2021 to April 2022, using a validated questionnaire to collect the data. The study included females (15 to 49 years) who had confirmed COVID infection. Results: A total of 132 females participated in the study. For 29 (22%) patients presenting with menstrual cycle changes, most common change was prolonged cycle (14%). An increase in menstrual volume was reported by 12%, where as 35% of patients experienced more pain during menstruation. Menstrual irregularities were significantly higher in severe infection (p-value 0.04). Conclusion: There were transient changes in menstruation in COVID-19-infected patients, with a higher probability of menstruation abnormalities among severely infected patients.